PTH-related protein and Type 1 PTH receptor mRNA expression in ventricular myocardial hypertrophy. Issue 3 (May 2005) - Halapas, Antony; Lembessis, Peter; Sourla, Antigone; Pantos, Costas; Cokkinos, Dennis V; Koutsilieris, Michael
Background: The parathyroid hormone (PTH)-related protein (PTHrP) and Type 1 PTH receptor (PTH-1.R) bioregulation system exerts positive inotropic and chronotropic actions on myocardium in  vivo, and it is implicated in cell––cell interactions, which can lead to myocardial hypertrophy.Objective: We analyzed the expression of PTHrP and PTH-1.R (mRNA and protein) in adult male Wistar rat ventricular myocardium after the induction of myocardial hypertrophy using aortic constricted and hyperthyroid models.Materials & methods: Expression of PTHrP and PTH-1.R mRNA was studied by semiquantitative reverse transcriptase polymerase chain reaction, while the nature of the polymerase chain reaction products was confirmed by direct DNA sequence. The expression of PTHrP and PTH-1.R in rat ventricular myocardium was confirmed using western blot and immunocytochemistry analysis.Results: The data showed that aortic banding-induced ventricular hypertrophy was associated with an increase in PTHrP mRNA expression, while hyperthyroid-induced ventricular hypertrophy was associated with PTH-1.R (mRNA and protein) overexpression in rat myocardium.Conclusion: Transcriptional changes of the PTHrP/PTH-1.R bioregulation system are differentially regulated in aortic constricting-induced and hyperthyroid-induced rat ventricular hypertrophy.